Assessing the utilization of the decision to implement a palliative goal for the treatment of cancer patients during the last year of life at Helsinki University Hospital: a historic cohort study. (2nd December 2019) - Hirvonen, Outi M.; Leskelä, Riikka-Leena; Grönholm, Lotta; Haltia, Olli; Rissanen, Antti; Tyynelä-Korhonen, Kristiina; Rahko, Eeva K.; Lehto, Juho T.; Saarto, Tiina
Abstract: Background: To avoid aggressive treatments at the end-of-life and to provide palliative care (PC), physicians need to terminate futile anti-cancer treatments and define the palliative goal of the treatment in time. This single center study assesses the practices used to make the decision that leads to treatment with a palliative goal, i.e., the PC decision and its effect on anti-cancer treatments at the end of life. Material and methods: Patients with a cancer diagnosis treated in tertiary hospital during 1st January 2013 – 31st December 2014 and deceased by the end of 2014 were identified in the hospital database ( N  = 2737). Of these patients, 992 were randomly selected for this study. The PC decision was screened from patient records, i.e., termination of cancer-specific treatments and a focus on symptom-centered PC. Results: The PC decision was defined in 82% of the patients during the last year of life (49% >30 days and 33% ≤30 days before death, 18% with no decision). The median time from the decision to death was 46 days. Systemic cancer therapy was given during the last month of life in 1%, 36% and 38% ( p  < .001) and radiotherapy 22%, 40% and 31% ( p  = .03) cases, respectively; referral to a PC unit was made in 62%, 22% and 11%, respectively ( p  < .001). In logistic regression analyses younger age, shorter duration of the disease trajectory and type of cancer (e.g., breast cancer) were associated with a lack or late timing of the PC decision. Conclusion: The decision to initiate a palliative goal for the treatment was frequently made for cancer patients but occurred late for every third patient. Younger age and certain cancer types were associated with late PC decisions, thus leading to anti-cancer treatments continuing until close to the death with low access to a PC unit.